UMP – leader of industry Centre of Excellent for Biotechnology - UMP, PNC
Universiti Malaysia Pahang (UMP) and Manipal International University (MIU) have been appointed to take charge of developing Industry Centre of Excellent (ICoE) for biotechnology industry that involved areas in chemical engineering, industries and food in Malaysia.